Differences in knee extensors` muscle-tendon unit passive stiffness, architecture, and force production in competitive cyclists versus runners - Cesanelli, L.; Kamandulis, S.; Eimantas, N.; Satkunskiene, D. (Journal of Applied Biomechanics, 2022)
To describe the possible effects of chronic specific exercise training, the present study compared the anthropometric variables, muscle-tendon unit (MTU) architecture, passive stiffness, and force production capacity between a group of competitive cyclists and runners. Twenty-seven competitive male cyclists (n = 16) and runners (n = 11) participated. B-mode ultrasound evaluation of the vastus lateralis muscle and patellar tendon as well as passive stiffness of the knee extensors MTU were assessed. The athletes then performed a test of knee extensor maximal voluntary isometric contractions. Cyclists displayed greater thigh girths, vastus lateralis pennation angle and muscle thickness, patellar tendon cross-sectional area, and MTU passive stiffness than runners (P < .05). Knee extensor force production capacity also differed significantly, with cyclists showing greater values compared with runners (P < .05). Overall, the direct comparison of these 2 populations revealed specific differences in the MTU, conceivably related to the chronic requirements imposed through the training for the different disciplines.